A solid acid catalyst and its application
By loading trivalent iron salt and divalent zinc salt on SiO2 support, a solid acid catalyst was prepared, which solved the problem of additives in isobutene superposition reaction, and achieved efficient and stable catalytic effect and cost reduction.
Patent Information
- Application Number
- CN202111642328.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2021-12-29
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2041-12-29
AI Technical Summary
Additives are required to be added to existing isobutene superposition reactions, resulting in increased production costs and complicated processes.
A solid acid catalyst with a solid acid catalyst with a trivalent iron salt and a divalent zinc salt is provided by supporting iron sulfate and zinc sulfate on the surface of the SiO2 support to provide suitable acidity and diffusive properties.
In the absence of additives, the catalytic activity, product selectivity and catalytic stability of the isobutylene superposition reaction are significantly improved, reducing production costs and simplifying the process flow.
Smart Images

Figure GDA0005105768340000061
Abstract
Description
Technical Field
[0001] The invention relates to the field of catalysts, and in particular to a solid acid catalyst and application thereof. Background Art
[0002] Isobutylene (IB) is an important industrial raw material and chemical intermediate. It can be divided into high-purity isobutylene (HPI, purity > 99.5%) and industrial isobutylene according to the purity of the raw material. Among them, high-purity isobutylene is mainly produced by processes such as isobutane dehydrogenation, tert-butyl alcohol dehydration and methyl tert-butyl ether (MTBE) cracking. The product obtained has high purity and is mainly used to produce high value-added products such as isoprene, methyl methacrylate, butyl rubber, etc. Industrial-grade isobutylene is mainly a liquefied gas by-product after atmospheric and vacuum distillation and catalytic cracking of crude oil. These by-products are separated by gas to obtain C4 mixed olefins containing isobutylene. Since the content of industrial-grade isobutylene is relatively low (content < 50%), it is usually used to produce methyl tert-butyl ether (MTBE), polybutene, tert-butyl alcohol and other products. Isobutylene is superimposed once to obtain the dimer C8 = (DIB).C8 = It can be used to produce octyl diphenylamine, octylamine, tert-octylphenol and other chemicals, and can also be hydrogenated to obtain isooctane. After secondary polymerization of isobutylene, a C 12 = (TIB) product, after hydrogenation, is a good solvent and can also be used as a diesel additive to produce fine chemicals such as calcium dodecyl sulfonate, dodecylphenol, dodecyl succinic acid, and dodecyl mercaptan. The product C after three times of isobutylene stacking 16 = (TEB) can be used to produce high-carbon alcohols, which are widely used in the production of various cosmetics, skin care products, emulsion additives, etc. Isobutylene that does not participate in the reaction can be used to produce maleic anhydride, and can also be recycled into the reactor for recycling.
[0003] Early olefin superposition reaction is a liquid-liquid phase reaction, and the catalyst is mostly a liquid acid represented by hydrofluoric acid, sulfuric acid, etc. The product purity obtained using sulfuric acid catalyst is low, not only separation and recovery are difficult and serious corrosion pipelines, but also the discharged wastewater will pollute the environment. Hydrofluoric acid catalyst has extremely strong toxicity and is not suitable for large-scale industrial production. Liquid acid catalysts have been eliminated by most companies at present because they cannot meet the requirements of modern industrial green environmental protection. Solid acid catalysts have the advantages of being safer, easy to control, easy to separate after reaction, and not producing a large amount of waste liquid, and have received more and more attention in recent years. The solid acid catalysts used for isobutylene superposition reaction mainly include solid phosphoric acid catalysts, zeolite molecular sieve catalysts and ion exchange resin catalysts. US 3132109 and US 3112350 disclose a catalyst of a paper cup impregnated with a phosphoric acid solution on a diatomaceous earth carrier, which has a high catalyst activity and can fully meet the needs of large-scale industrial production. EP0371938 discloses a method for synthesizing an industrial mixed C4 olefin superposition solid phosphoric acid catalyst. The catalyst is based on SiO2 as a carrier, impregnated with a 42wt% orthophosphoric acid solution, dried at 170°C, and then calcined at 325-525°C. It needs to be moistened with water vapor before use. The catalyst exhibits the highest activity after being calcined at 350°C. CN1810373A discloses a catalyst for selective dimerization of isobutylene. The catalyst is prepared by vacuum impregnating a silica carrier into a 50% phosphoric acid solution, drying at 120°C, and calcining at 400°C. The free phosphoric acid is calculated as 28.65wt% in terms of P2O5. It is used for selective dimerization of isobutylene to produce high-octane gasoline at 120°C, 4.5MPa, and a liquid phase space velocity of 2h -1 Under the reaction conditions, the continuous operation lasted for 1008h, the isobutylene conversion rate reached 95.5%, the isooctene selectivity was 86.0%, the isooctene yield was 82.13%, and there was no obvious mudding phenomenon after the catalyst was removed, and the mechanical strength was good. CN106861731A discloses a catalyst for isobutylene and a preparation method. The catalyst carrier is a composite carrier containing zinc oxide-aluminum oxide, and the active components include iron sulfate and nickel sulfate. The composite carrier zinc and aluminum are evenly dispersed and have a high specific surface area. The isobutylene polymerization reaction activity and selectivity are high. After the reaction, the catalyst is easy to separate from the product, and the production cycle is long. CA2435590 discloses an Amberlyst-15 catalyst after different metal ion exchange for isobutylene dimerization reaction. Studies have found that when Na + Replaces 50% of H on Amberlyst-15 + After that, the isobutylene conversion rate dropped from 99.7% to 78%, and the dimer selectivity increased from 19% to 63%. + Replaces 50% of H on Amberlyst-15 +After that, the selectivity of dimer can reach 90%. + Na + After substitution, the polymerization rate decreased significantly. In the isobutylene dimerization reaction carried out on a raw material composition of 100% isobutylene, 80% Na + The Amberlyst-15 catalyst obtained by the exchange has the best performance, with isobutylene conversion and dimer selectivity reaching 67% and 82% respectively, and C8 = The products are all 2,4,4-trimethylpentene, but its selectivity needs to be improved. Studies have found that adding low-carbon alcohols or polar inhibitors to the raw materials can also greatly improve the selectivity of isobutylene dimerization products of sulfonic acid resin catalysts. For example, adding a certain amount of methanol to the isobutylene raw material, the isobutylene polymerization reaction and etherification reaction are carried out simultaneously, which can greatly reduce the formation of trimers, but at the same time it will cause a large amount of isobutylene to be converted into MTBE, reducing the yield of the main product isooctene, and after the reaction, a post-processing process of separating the inhibitor from the product is required, which increases the process flow and production costs.
[0004] In summary, the current isobutylene polymerization reaction to prepare its dimer product requires a solid acid catalyst with stable morphology, high selectivity and conversion rate, and no additives. Summary of the invention
[0005] The object of the present invention is to provide a solid acid catalyst to solve the defect in the prior art that additives need to be added when isobutylene is superposed to prepare its dimer product.
[0006] To achieve the above object, the present invention provides a solid acid catalyst, comprising 95-99.5wt% of SiO2 carrier and 0.5-5.0wt% of active components, wherein the active components are trivalent iron salt and divalent zinc salt.
[0007] The solid acid catalyst of the present invention, wherein the molar proportion of iron is n Fe / n Fe+Zn =0.05~0.95.
[0008] The solid acid catalyst of the present invention has an average pore size of 5 to 15 nm, an average pore volume of 0.8 to 1.2 mL / g, and a specific surface area of 200 to 380 m 2 / g.
[0009] The solid acid catalyst of the present invention has an average pore size of 7 to 9 nm, an average pore volume of 0.9 to 1.1 mL / g, and a specific surface area of 300 to 340 m 2 / g, particle size is 10~80 mesh.
[0010] The solid acid catalyst of the present invention comprises 96.5-98.5 wt% of SiO2 carrier and 1.5-3.5 wt% of active component, wherein the molar proportion of iron is n Fe / n Fe+Zn =0.2~0.7.
[0011] The solid acid catalyst of the present invention, wherein the molar proportion of iron is n Fe / n Fe+Zn =0.3~0.5
[0012] In the solid acid catalyst of the present invention, the trivalent iron salt is ferric sulfate, and the divalent zinc salt is zinc sulfate.
[0013] To achieve the above object, the present invention also provides an application of the solid acid catalyst in a superposition reaction with pure isobutylene or isobutylene in mixed C4 as a reactant.
[0014] The application of the present invention, wherein the reaction conditions of the superposition reaction are reaction temperature 50-70°C, reaction pressure 1.5-2.5MPa, isobutylene liquid space velocity 1.5-3.5h -1 .
[0015] The beneficial effects of the present invention are:
[0016] The solid acid catalyst provided by the present invention is prepared by loading zinc sulfate and / or ferric sulfate on the surface of a SiO2 carrier. The catalyst has suitable acidity and diffusion properties, and exhibits good catalytic activity, product selectivity and catalytic stability for the preparation of isobutylene dimers by isobutylene superposition without any addition of low-carbon alcohols or polar inhibitors in the raw materials, and has high practical applicability in industry. DETAILED DESCRIPTION
[0017] The present invention is described in detail below by way of examples. It is necessary to point out that the following examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. Those skilled in the art in this field can make some non-essential improvements and adjustments to the present invention based on the above content of the present invention.
[0018] A solid acid catalyst comprises 95-99.5wt% of SiO2 carrier and 0.5-5.0wt% of active components, wherein the active components are trivalent iron salt and divalent zinc salt.
[0019] The present invention selects SiO2 as a carrier. The SiO2 carrier has an amorphous structure, which can provide a relatively suitable large surface area, has relatively high strength and good thermal stability, and is low in price.
[0020] The solid acid catalyst of the present invention, wherein the molar proportion of iron in the catalyst is n Fe / n Fe+Zn =0.05~0.95.
[0021] The solid acid catalyst of the present invention has an average pore size of 5 to 15 nm, an average pore volume of 0.8 to 1.2 mL / g, and a specific surface area of 200 to 380 m 2 / g.
[0022] The solid acid catalyst of the present invention has an average pore size of 7 to 9 nm, an average pore volume of 0.9 to 1.1 mL / g, and a specific surface area of 300 to 340 m 2 / g, and the particle size is 10 to 80 mesh, preferably 40 to 60 mesh.
[0023] The pore size and pore volume of SiO2 have a great influence on the conversion rate of isobutylene and the selectivity of large molecular size products. The catalyst prepared by the large pore size carrier is conducive to the external diffusion of polymerization intermediates to a certain extent, inhibiting their further deep stacking to generate high carbon products, which is conducive to improving the selectivity of dimerization products. However, it will also reduce the conversion rate of the raw materials because the size distribution of the substances that can enter and exit becomes wider, which relatively dilutes the concentration of the raw materials.
[0024] The solid acid catalyst of the present invention comprises 96.5-98.5 wt% of SiO2 carrier and 1.5-3.5 wt% of active component, wherein the molar proportion of iron is n Fe / n Fe+Zn =0.2~0.7.
[0025] The solid acid catalyst of the present invention, wherein the molar proportion of iron is n Fe / n Fe+Zn =0.3~0.5.
[0026] In the solid acid catalyst of the present invention, the trivalent iron salt is ferric sulfate, and the divalent zinc salt is zinc sulfate.
[0027] Zinc sulfate, as a preferred metal salt active ingredient, shows a high conversion rate in the isobutylene polymerization reaction, but the selectivity of the target product dimer (a mixture of 2,4,4-trimethyl-1-pentene and 2,4,4-trimethyl-2-pentene) is inferior to that of the commercial isobutylene dimerization catalyst. By adding a certain amount of iron sulfate to the active ingredient, the selectivity of the dimer product can be improved without changing the conversion rate of isobutylene.
[0028] The preparation method of the solid acid catalyst comprises: immersing the SiO2 carrier in a solution containing a metal salt active component and drying the solution.
[0029] An application of the solid acid catalyst in a superposition reaction using pure isobutylene or isobutylene in mixed C4 as a reactant.
[0030] The carbon number of the isobutylene polymer prepared by the superposition reaction is 8 to 16, among which the dimerization product (a mixture of 2,4,4-trimethyl-1-pentene and 2,4,4-trimethyl-2-pentene) has a higher selectivity, accounting for 52.5 to 90.0%.
[0031] The application of the present invention, wherein the reaction conditions of the superposition reaction are reaction temperature 50-70°C, reaction pressure 1.5-2.5MPa, isobutylene liquid space velocity 1.5-3.5h -1 .
[0032] Example 1
[0033] A solid acid catalyst comprising 98.0 wt% of SiO2 carrier and 2.0 wt% of iron sulfate and zinc sulfate, Fe / n Fe+Zn is 0.35.
[0034] The specific surface area of SiO2 is 337m 2 / g, the average pore diameter is 7.43nm, the average pore volume is 1.0659mL / g, and the particle size is 40 mesh.
[0035] The preparation method of the solid acid catalyst is as follows: SiO2 is immersed in a solution containing a metal salt active component and then dried.
[0036] 25 ml of the prepared catalyst was used to prepare isobutylene oligomers. The preparation method was as follows: at a reaction temperature of 50°C, a reaction pressure of 2.0 MPa, and an isobutylene liquid space velocity of 3.0 h -1 Catalysis under certain conditions can produce the product.
[0037] Analysis of the polymerization product:
[0038] After the isobutylene polymerization reaction is completed, the reaction products enter the gas-liquid separator for separation, and the obtained gas phase products are introduced into the chromatograph for online detection, and the real-time isobutylene reaction conversion rate is calculated. Specifically: the composition of the raw materials and gas phase products is analyzed using an SP-6890 chromatograph. The analytical column is a special analytical column for alumina capillaries, the column temperature is 60°C, and the hydrogen flame detector is used. After the reaction liquid phase products are collected, they are analyzed using an SP-6890 chromatograph. The analytical column model of the chromatograph is an HP-PONA chromatographic column and an FID detector. The column temperature starts to rise from 35°C, the heating rate is 2°C / min, and the program temperature rises to 270°C and stops. The data uses N2000 +The chromatography data workstation is used for processing by area normalization method. The composition of each component in the liquid phase product is calculated by the peak area of each component.
[0039] Analysis showed that the isobutylene conversion was 92.0 wt%, the dimerization product selectivity was 86.47 wt%, and the trimerization product selectivity was 12.25 wt%.
[0040] Example 2
[0041] A solid acid catalyst comprising 98.5 wt% of SiO2 carrier and 1.5 wt% of iron sulfate and zinc sulfate, Fe / n Fe+Zn is 0.35.
[0042] The specific surface area of SiO2 is 352m 2 / g, the average pore diameter is 6.38nm, the average pore volume is 0.916mL / g, and the particle size is 40 mesh.
[0043] The catalyst preparation method, polymer preparation method and polymer product analysis are the same as in Example 1.
[0044] Analysis showed that the isobutylene conversion was 81.0 wt%, the dimer selectivity was 73.24 wt%, and the trimer selectivity was 20.73 wt%.
[0045] Example 3
[0046] A solid acid catalyst comprising 97.5wt% of SiO2 carrier and 2.5wt% of iron sulfate and zinc sulfate, n Fe / n Fe+Zn is 0.35.
[0047] The specific surface area of SiO2 is 337m 2 / g, the average pore diameter is 7.43nm, the average pore volume is 1.0659mL / g, and the particle size is 10 mesh.
[0048] The catalyst preparation method, polymer preparation method and polymer product analysis are the same as in Example 1.
[0049] Analysis showed that the isobutylene conversion was 88.5 wt%, the dimer olefin selectivity was 83.33 wt%, and the trimer selectivity was 13.60 wt%.
[0050] Table 1 shows the acid strength distribution of the catalysts described in Examples 1, 2 and 3 measured by n-butylamine titration. As can be seen from the table, there are no strong acid centers (H0≤-3.0) on the surfaces of the three catalysts; the catalyst in Example 1 has more medium-strength acid centers (-3.0≤H0≤2.27).
[0051] Table 1
[0052]
[0053] Example 4
[0054] A solid acid catalyst comprising 96.5wt% of SiO2 carrier and 3.5wt% of iron sulfate and zinc sulfate, n Fe / n Fe+Zn is 0.35.
[0055] The specific surface area of SiO2 is 285m 2 / g, the average pore diameter is 11.00nm, the average pore volume is 1.1274mL / g, and the particle size is 40 mesh.
[0056] The catalyst preparation method, polymer preparation method and polymer product analysis are the same as in Example 1.
[0057] The analysis showed that the isobutylene conversion was 87.67 wt%, the dimer olefin selectivity was 86.25 wt%, and the trimer selectivity was 11.62 wt%.
[0058] Example 5
[0059] A solid acid catalyst comprising 97.0 wt% of SiO2 carrier and 3.0 wt% of iron sulfate and zinc sulfate, Fe / n Fe+Zn is 0.35.
[0060] The specific surface area of SiO2 is 209m 2 / g, the average pore diameter is 14.59nm, the average pore volume is 1.1878mL / g, and the particle size is 40 mesh.
[0061] The catalyst preparation method, polymer preparation method and polymer product analysis were the same as in Example 1. The isobutylene conversion was 63.03 wt%, the dimer olefin selectivity was 56.39 wt%, and the trimer selectivity was 19.22 wt%.
[0062] Example 6
[0063] A solid acid catalyst comprising 97.5wt% of SiO2 carrier and 2.5wt% of iron sulfate and zinc sulfate, n Fe / n Fe+Zn They are 0, 0.2, 0.5 and 0.8 respectively.
[0064] The specific surface area of SiO2 in the solid acid catalyst is 337 m 2 / g, the average pore diameter is 7.43nm, the average pore volume is 1.0659mL / g, and the particle size is 40 mesh.
[0065] The preparation method of the solid acid catalyst is the same as that of Example 1.
[0066] The solid acid catalyst is used to prepare an isobutylene stack. The preparation method of the isobutylene stack is: at a reaction temperature of 67°C, a reaction pressure of 3.0 MPa, and an isobutylene liquid space velocity of 1.2 h -1 Catalytic conditions.
[0067] The analysis of the polymer product was the same as in Example 1.
[0068] The conversion of isobutylene and the selectivity of isobutylene stack are shown in the following table.
[0069] <![CDATA[n Fe / n (Fe+Zn) ]]> Isobutylene conversion Dimer selectivity Trimer selectivity 0 86.5wt% 70.4wt% 28.6wt% 0.2 86.8wt% 80.5wt% 18.6wt% 0.5 85.9wt% 81.7wt% 17.9wt% 0.8 86.3wt% 76.3wt% 20.5wt%
[0070] Example 7
[0071] A solid acid catalyst comprising 97.5wt% of SiO2 carrier and 2.5wt% of iron sulfate and zinc sulfate, n Fe / n Fe+Zn is 0.35.
[0072] The specific surface area of SiO2 in the solid acid catalyst is 370.8 m 2 / g, the average pore volume is 0.8328mL / g, the pore diameter is 6.02nm, and the particle size is 80 mesh.
[0073] The catalyst preparation method, polymer preparation method and polymer product analysis are the same as in Example 1.
[0074] The analysis showed that the isobutylene conversion was 73.06 wt%, the dimer olefin selectivity was 79.24 wt%, and the trimer selectivity was 20.04 wt%.
[0075] Comparative Example 1
[0076] A solid phosphoric acid catalyst, the specific surface area of the silica carrier is 268m 2 / g, average pore volume 1.18mL / g, pore diameter 11.24nm, the carrier is dried at 120°C for 12 hours, 500g of 50% (weight) phosphoric acid solution is added to a 500ml round-bottom flask, the above 200g silica carrier is added, impregnated for 8 hours under negative pressure, dried for 8 hours at 100-120°C in an oven, calcined for 4 hours at 350°C in a muffle furnace, and the impregnated carrier is further impregnated with 50% (weight) phosphoric acid solution for a second time, impregnated for 8 hours under negative pressure, dried for 8 hours at 100-120°C, and calcined at 350°C to obtain a catalyst. The free phosphoric acid is 30% (weight) in terms of P2O5.
[0077] The isobutylene oligomer is prepared by using the 25 ml solid acid catalyst. The preparation method of the isobutylene oligomer is as follows: the reaction pressure is 4.5 MPa, the reaction temperature is 120° C., and the isobutylene liquid space velocity is 2.0 h -1 .
[0078] After the isobutylene polymerization reaction is completed, the reaction products enter the gas-liquid separator for separation, and the obtained gas phase products are introduced into the chromatograph for online detection, and the real-time isobutylene reaction conversion rate is calculated. Specifically: the composition of the raw materials and gas phase products is analyzed using an SP-6890 chromatograph. The analytical column is a special analytical column for alumina capillaries, the column temperature is 60°C, and the hydrogen flame detector is used. After the reaction liquid phase products are collected, they are analyzed using an SP-6890 chromatograph. The analytical column model of the chromatograph is an HP-PONA chromatographic column and an FID detector. The column temperature starts to rise from 35°C, the heating rate is 2°C / min, and the program temperature rises to 270°C and stops. The data uses N2000 + The chromatography data workstation is used for processing by area normalization method. The composition of each component in the liquid phase product is calculated by the peak area of each component.
[0079] The catalyst evaluation results are as follows: the isobutylene conversion rate reaches 95.50%, and the isooctene selectivity is 86.00%.
[0080] Comparative Example 2
[0081] A zinc oxide-aluminum oxide composite carrier loaded with active metal iron sulfate and nickel sulfate catalysts, the composite carrier has a specific surface area of 276m 2 / g, the composite carrier includes 25.0wt% zinc oxide containing zinc aluminum spinel, 72.0wt% aluminum oxide, and the contents of other components are 0.4wt% P2O5, 1.2wt% K2O, and 1.5wt% MgO. Take 12.7g of ferric sulfate hexahydrate and 11.1g of nickel sulfate hexahydrate and add them to 30ml of distilled water, then dilute with deionized water to prepare an impregnation solution, take 100g of the composite carrier containing zinc oxide-alumina for equal volume impregnation, and after impregnation, the carrier is dried in an oven at 100-120℃ for 6h, and then calcined in a muffle furnace at 450℃ for 4h to obtain an isobutylene polymerization catalyst. The catalyst mainly consists of 10.0wt% ferric sulfate, 2.5wt% nickel sulfate, and 87.5wt% of the composite carrier containing zinc oxide-alumina.
[0082] The isobutylene oligomer is prepared by using the 25 ml solid acid catalyst. The preparation method of the isobutylene oligomer is as follows: the reaction pressure is 3.0 MPa, the reactor temperature is 100° C., and the feed volume space velocity is 6.0 h -1 .
[0083] After the isobutylene polymerization reaction is completed, the reaction products enter the gas-liquid separator for separation, and the obtained gas phase products are introduced into the chromatograph for online detection, and the real-time isobutylene reaction conversion rate is calculated. Specifically: the composition of the raw materials and gas phase products is analyzed using an SP-6890 chromatograph. The analytical column is a special analytical column for alumina capillaries, the column temperature is 60°C, and the hydrogen flame detector is used. After the reaction liquid phase products are collected, they are analyzed using an SP-6890 chromatograph. The analytical column model of the chromatograph is an HP-PONA chromatographic column and an FID detector. The column temperature starts to rise from 35°C, the heating rate is 2°C / min, and the program temperature rises to 270°C and stops. The data uses N2000 + The chromatography data workstation is used for processing by area normalization method. The composition of each component in the liquid phase product is calculated by the peak area of each component.
[0084] The catalyst evaluation results are as follows: the isobutylene conversion rate reaches 90.80%, the dimerization olefin selectivity is 72.80%, and the trimerization olefin selectivity is 28.75%.
[0085] Comparative Example 3
[0086] Comparative Example 3 of the present invention illustrates the effect of the inhibitor on the selectivity of the superposition reaction. Isobutylene oligomers are prepared using Amberlust-15 resin catalyst. The preparation method of the isobutylene oligomers is as follows: the reaction pressure is 4.5 MPa, the feed volume space velocity is 3.0 h -1 , reactor temperature 65°C.
[0087] The materials after the reaction include liquid products and gaseous logistics. The liquid products pass through the gas-liquid separator, and enter the liquid collector. The carbon composition of the reaction products is regularly sampled and analyzed. The gaseous logistics, i.e. the unreacted tail gas, regularly enters the online gas chromatography for analysis.
[0088] Using ethanol as an inhibitor and under the action of Amberlyst 35 cation exchange resin catalyst, the relationship between the isobutylene polymerization product and the alcohol-olefin ratio is shown in the table below.
[0089] n(alcohol) / n(olefin) Isobutylene conversion rate wt% Dimer selectivity wt% ETBEwt% 0 100 52.1 0 0.2 83.1 83.05 40 0.4 73.7 86.1 65 0.7 86.9 92.9 85
[0090] The results of catalyst evaluation are as follows: when n(alcohol) / n(olefin) is 0, 0.2, 0.4, 0.7, the isobutylene conversion is 100wt%, 83.1wt%, 73.7wt%, 86.9wt%, respectively; the dimer olefin selectivity is 52.1wt%, 83.05wt%, 86.1wt%, 92.9wt%, respectively. With the addition of inhibitor, the proportion of dimers in the superposition product increases, but the content of ethyl tert-butyl ether (ETBE) also increases, resulting in a decrease in the yield of dimers and increasing the difficulty of product separation.
[0091] Of course, the present invention may have many other embodiments. Without departing from the spirit and essence of the present invention, technicians familiar with the field may make various corresponding changes and deformations based on the present invention, but these corresponding changes and deformations should all fall within the scope of protection of the claims of the present invention.
Claims
1. A solid acid catalyst for a superposition reaction using pure isobutylene or isobutylene in a mixed C4 as a reactant, characterized in that: The catalyst comprises 95-99.5 wt% of SiO2 carrier and 0.5-5.0 wt% of active components, wherein the active components are trivalent iron salt and divalent zinc salt; the molar proportion of iron in the catalyst is n Fe / n Fe+Zn = 0.05~0.
95.
2. The solid acid catalyst for the superposition reaction using pure isobutylene or isobutylene in mixed C4 as a reactant according to claim 1, characterized in that: The average pore size of the SiO2 carrier is 5-15 nm, the average pore volume is 0.8-1.2 mL / g, and the specific surface area is 200-380 m 2 / g.
3. The solid acid catalyst for the superposition reaction using pure isobutylene or isobutylene in mixed C4 as a reactant according to claim 1, characterized in that: The average pore size of the SiO2 carrier is 7-9 nm, the average pore volume is 0.9-1.1 mL / g, and the specific surface area is 300-340 m 2 / g, particle size is 10~80 mesh.
4. The solid acid catalyst for the superposition reaction using pure isobutylene or isobutylene in mixed C4 as a reactant according to claim 1, characterized in that: The invention comprises 96.5-98.5 wt% of SiO2 carrier and 1.5-3.5 wt% of active component, wherein the molar proportion of iron element is n Fe / n Fe+Zn = 0.2~0.
7.
5. The solid acid catalyst for the superposition reaction using pure isobutylene or isobutylene in mixed C4 as a reactant according to claim 4, characterized in that: The molar percentage of iron Fe / n Fe+Zn = 0.3~0.
5.
6. The solid acid catalyst for the superposition reaction using pure isobutylene or isobutylene in mixed C4 as a reactant according to claim 1, characterized in that: The trivalent iron salt is ferric sulfate, and the divalent zinc salt is zinc sulfate.
7. The solid acid catalyst for the superposition reaction using pure isobutylene or isobutylene in mixed C4 as a reactant according to claim 1, characterized in that: The reaction conditions of the superposition reaction are reaction temperature 50-70°C, reaction pressure 1.5-2.5 MPa, isobutylene liquid space velocity 1.5-3.5 h -1 .
Citation Information
Patent Citations
Catalyst for isobutene oligomerization and preparation method thereof
CN106861731A
Catalyst for selective dimerization of isobutene
CN1810373A
A method of making a catalyst based on silicon dioxide and phosphoric acid
EP0371938A1
Polymerization of olefins using a solid phosphoric acid catalyst
US3112350A
Polymerization catalyst comprising phosphoric acid and siliceous materials
US3132109A